KRT17 from skin cells with high glucose stimulation promotes keratinocytes proliferation and migration - Zhou, Peng; Feng, Haijun; Qin, Wenhui; Li, Qin (Frontiers in Endocrinology, 2023)
Impaired diabetic wound healing is an important issue in diabetic complications. Proliferation and migration of keratinocytes are major processes of skin wound repair after injury. However, hyperkeratosis can affect the speed of wound healing. Based on the results of preliminary experiments on increased KRT17 expression after high glucose stimulation of human skin tissue cells, a cell model of human immortalized keratinocyte (HaCaT) stimulation with different concentrations of KRT17 was established in vitro, and the promotion in cell proliferation and migration were discovered. KRT17 silencing promoted diabetic wound healing in the db/db diabetic wound model. Transcriptome sequencing (RNA-seq) was performed on HaCaT cells after KRT17 stimulation, and analysis showed significant enrichment in the PI3K-AKT signaling pathway, in which the regulation of cell c-MYB mRNA, a key molecule regulating cell proliferation and migration, was significantly upregulated. In vitro assays showed increased c-MYB expression and enhanced pAKT activity after HaCaT cell stimulation by KRT17. We speculate that KRT17 is upregulated under high glucose and promotes keratinocyte proliferation and migration caused hyperkeratosis, through the c-MYB/PI3K-AKT pathway, contributing to delayed wound healing.